Agronomic approach to evaluate the nitrogen use efficiency of liquid, solid, and composted swine manures in corn–soybean rotation - Niu, Junjie; Zhang, Tiequan; Wen, Guang; Zheng, Zhiming; Jia, Yu; Tan, Chin S.; Welackey, Tom (Frontiers in Environmental Science, 2023)
Evaluating the nitrogen (N) use efficiency of animal manure is essential to optimize application for profitable crop production without impairing the environment. A four-year field study was conducted under corn (Zea mays L.)-soybean (Glycine max L.) rotation in a Brookston clay loam soil using the yield control approach. Treatments included inorganic fertilizer (IN), liquid (LM), solid (SM) and composted (CM) swine manure applied at the rate equivalent to available N of 200 kg ha-1, and a non-fertilization control (CT). Seven N use indices were employed to evaluate N use efficiency. LM obtained comparable corn yields relative to IN. Corn yield in SM was inconsistent from one year to another, and CM had minimal agronomical value in our study. Soybean with IN posed the highest grain yields of 3468 and 3761 kg ha-1 in 2005 and 2007, respectively. In contrast to grain yield and total N uptake, the gain N removal of either corn or soybean was comparable between the two alternative years. The distinctions of N supply dynamics of manures and influences on yield, grain N removal and total above-ground plant N uptake of corn were well discriminated by N use efficiency (NUE), N uptake efficiency (NUpE), N utilization efficiency (NUtE), N agronomic efficiency (NAE) and N recovery efficiency (NRE), but not by N physiological efficiency (NPE) and N harvest index (NHI). Legacy effects on soybean yield from the preceding corn were detected by NAE and NRE. Based on grain yield in conjunction with N use efficiency parameters, the IN performed the best, followed by LM. The NUE, NUpE, NUtE, NAE and NRE parameters, used to evaluate chemical fertilizer N, were also applicable to evaluate manure N efficiency.